Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Telkom Indonesia Divisi Regional VII - Ilham Himawan; Idrus Taba; Andi Reni (Hasanuddin Journal of Business Strategy, 2019)
This study aims to determine the relationship of leadership style and organizational culture on employee performance through job satisfaction as intervening variables in Telkom Indonesia Regional VII Division. The population of the study is based on managerial & staff job positions consisting of 62 respondences from 161 full-time employees of Indonesia state-owned telecommunication company, Telkom Indonesia Regional VII Division. This research used quantitive methods. The primary data were collected by the questionnaire as the instrument to prove the results of the study. By using Smart Partial Least Squares (PLS), the analysis of collected data revealed and to test the hypotheses. According to the findings of this research supported the positive effect of leadership style, organizational culture, and job satisfaction through employee performances. The hypotheses analysis in the study has no significant effect of leadership style on employee performance, whereas job satisfaction as partial mediating.